Construção identitária de alunos guianenses que estudam em Bonfim-RR - Fonseca, Natália Barroncas da (2015)
This study aims to investigate how a socio-cultural-linguistic border context influences the constitution of the individual that lives and study there. This work is oriented under the bias of Applied Linguistics, a mixed area of research that is interested in new theories and dialogues with other areas of knowledge such as Cultural Studies and Sociolinguistics. This research is relevant to the academic community and to all the teachers that work in this educational system, by raising questions about linguistic minorities individuals, residents on the border who live and interact in an environment of cultural dimensions that moves bidirectionally and also complement each other, in the perspective of transculturality. This is an ethnographic study with predominantly qualitative research approach. The records were collected through participant observation, field diary and semi-structured interviews recorded in audio only with the permission of the individuals or their legal guardians. A total of 10 individuals were interviewed, 8 students, 1 teacher and 1 secretary of the school. The analysis undertaken indicated the marking of difference and identity of students by language.